2021
DOI: 10.1186/s12966-021-01198-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and lifestyle on severe COVID-19 risk in 279,455 adults: a case control study

Abstract: Background The impact of cardiorespiratory fitness (CRF) and other lifestyle-related factors on severe COVID-19 risk is understudied. The present study aims to investigate lifestyle-related and socioeconomic factors as possible predictors of COVID-19, with special focus on CRF, and to further study whether these factors may attenuate obesity- and hypertension-related risks, as well as mediate associations between socioeconomic factors and severe COVID-19 risk. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 44 publications
1
66
0
3
Order By: Relevance
“…Six studies involving 130,774 cases (77,435 physically active cases and 53,339 control cases) were included. 8 , 14 , 16 , 17 , 18 , 19 The random‐effect model showed that PA was associated with reduction in COVID‐19 ICU admissions compared with control (RR = 0.65, 95% CI 0.52–0.81, P = 0.0001). The value of I 2 = 73% indicated that significant heterogeneity exists in the included studies ( P = 0.0001; Figure 3a ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Six studies involving 130,774 cases (77,435 physically active cases and 53,339 control cases) were included. 8 , 14 , 16 , 17 , 18 , 19 The random‐effect model showed that PA was associated with reduction in COVID‐19 ICU admissions compared with control (RR = 0.65, 95% CI 0.52–0.81, P = 0.0001). The value of I 2 = 73% indicated that significant heterogeneity exists in the included studies ( P = 0.0001; Figure 3a ).…”
Section: Resultsmentioning
confidence: 98%
“… 26 Additionally, it has a protective impact on COVID‐19 risk factors such as obesity and hypertension. 9 , 14 Furthermore, we previously reported that a sedentary lifestyles increase the risk of COVID‐19 severity and mortality. 16 Further, high hospitalisation rates have been reported in patients with less cardiorespiratory fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steps for retrieval and inclusion are shown in Fig 1 . The characteristics of the literature are listed in Table 1. Among the 17 studies, 3 were from North America [10,19,20], 7 were from Asia [11,12,21,22,23,24,25], 6 were from Europe [26,27,28,29,30,31], and 1 was from Oceania [32]. The NOS was used to score the included studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…VO 2 max is the highest possible rate of oxygen consumption during a physically intense whole-body activity, and an important factor for many types of physical performance. It has also been linked to several health-related outcomes, with a low capacity being strongly associated with increased risk for cardiovascular disease, the metabolic syndrome, a negative influence on cognitive function, and more recently, severe Covid-19 [ 1 5 ]. In a scientific statement from the American Heart Association, the inclusion of measurement of VO 2 max in clinical practice is urged for to provide the clinicians with vital possibilities to improve patient risk management and health [ 6 ].…”
Section: Introductionmentioning
confidence: 99%